Pengaruh Ekstrak Rimpang Alang-alang (Imperata cylindrica L.) pada Bobot Kering dan Persen Penutupan Gulma - Tamin, Argi Zhafran; Supriyatdi, Dedi; Syofian, Mirodi (Jurnal Agro Industri Perkebunan, 2017)
The use of herbicides has a negative impact on the environment so an environmentally friendly herbicide is needed. Alang-alang that are available in almost every area has a content of tannins in the form of allelopathy potential for weed control. The objective of the research is to know the percent of weed coverage due to the application of alang-alang bioherbicide.Concentration levels were tested in this research are: 5%, 10%, 15%, and 20%. The research was arranged in a randomized block design that has five replication. Variables observed were the dry weight of weeds and percent of weed coverage. The results of this research showed that all various concentrations have not affected in controlling weeds and percent of weed coverage. Keywords: allelopathy, bioherbicide, weed control